2005
DOI: 10.1093/pcp/pci127
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm of Circumnutation in Inflorescence Stems of Arabidopsis

Abstract: We investigate the modulation of circumnutation in inflorescence stems of Arabidopsis to determine the circadian regulation of circumnutation. Under constant light conditions (LL), circumnutation speed in wild-type plants fluctuates, with the phase of the highest speed at subjective dawn; the period length is close to 24 h. toc1 appears to shorten the period and elf3 causes an arrhythmic phenotype in circumnutation speed in LL, suggesting that a common circadian clock may control both circumnutation speed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 25 publications
5
31
0
Order By: Relevance
“…26 The circadian character of circumnutations was described in the hypocotyl of Arabidopsis thaliana seedlings. 9 Based on a genetic analysis (using toc-1, elf3 mutants and the wild-type Arabidopsis plants) Niinuma et al 27 revealed circadian regulation of circumnutation speed in inflorescence stems, with period length close to 24 h.…”
Section: Daily Circadian and Infradian Variability Of Circumnutationmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The circadian character of circumnutations was described in the hypocotyl of Arabidopsis thaliana seedlings. 9 Based on a genetic analysis (using toc-1, elf3 mutants and the wild-type Arabidopsis plants) Niinuma et al 27 revealed circadian regulation of circumnutation speed in inflorescence stems, with period length close to 24 h.…”
Section: Daily Circadian and Infradian Variability Of Circumnutationmentioning
confidence: 99%
“…29 In Arabidopsis inflorescence stem investigations of elf3 and toc1 mutants demonstrated that circumnutation is one of the outputs controlled by circadian clock. 27,58 …”
Section: Mutants In Research On the Circumnutation Mechanismmentioning
confidence: 99%
“…Characterization of clock mutants, elf3 and toc1 demonstrated that circumnutation is one of the outputs controlled by circadian clock (Niinuma et al 2005). The modulation of circumnutation speed in inflorescence stem of wild-type is rhythmic with the phases of highest and lowest speed at subjective dawn and dusk, respectively ( Figure 2D, E).…”
Section: Circumnutationmentioning
confidence: 97%
“…Photoperiodic flowering, mRNA stability (Lidder et al 2005), starch degradation and maltose metabolism (Lu et al 2005), photosynthesis (Dodd et al 2005a), Ca 2ϩ level (Dodd et al 2005b reviewed) and organ movements (Niinuma et al 2005;Someya et al 2006) have been shown to be controlled by the circadian clock. Among these, the regulation of flowering time has been well characterized and summarized in other recent reviews (Hayama and Coupland, 2003;Salome and McClung, 2004;Calvino et al 2005;Mizoguchi et al 2006).…”
Section: Organ Movement As One Of the Clockcontrolled Outputs In Plantsmentioning
confidence: 99%
See 1 more Smart Citation